2018
DOI: 10.21037/tcr.2018.06.07
|View full text |Cite
|
Sign up to set email alerts
|

Up to 5 years outcomes following intraoperative radiotherapy for early breast cancer

Abstract: Background: Whole breast radiation therapy (WBRT) is the standard of care for early breast cancer after lumpectomy, but it has side effects. For elderly women with good prognostic cancer, intra-operative radiotherapy (IORT) is an alternative. We report our results with IORT. Methods: We performed a retrospective cohort study to observe clinical outcomes after IORT, between 2012 and 2017. Patients had inclusion criteria for RIOP INCA (French national institute of cancer) (group A) or for TARGIT E (group B).Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…A French retrospective study by d'Illiers et al found that the rate of severe infection was 3.3% [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A French retrospective study by d'Illiers et al found that the rate of severe infection was 3.3% [32].…”
Section: Discussionmentioning
confidence: 99%
“…All these patients were treated with intravenous antibiotics and drainage [31]. A French retrospective study by d'Illiers et al found that the rate of severe infection was 3.3% [32].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the incidence of seroma was 6.0% and the infection rate was 5.0%; the infection rate was thus slightly higher than that in the TARGIT-A study (Table 4), but was comparable to the matched patients undergoing BCS over the same period. The wound infection rate arising from IORT varies significantly in the currently available studies, ranging from 2.3% to 13.6% (27)(28)(29). This difference might be attributable to the different radiotherapy equipment and methods used in the studies, and to the effect that variable patient characteristics, surgical procedures, and postoperative therapies might have had on toxicity and side effects.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, in IORT, no results were reported regarding drainage tube removal time, length of hospitalization, and post-operative complications. However, IORT had promising results, both in terms of saving healthy tissue and local control (74% to 100% at 5 years) and 96.2% disease-free survival ( 101 , 103 ). The local relapse prompted a series of clinical trials and studies to investigate whether localized IORT could be as efficient at preventing recurrence at local site as standard postoperative radiotherapy of the whole breast while also being more patient-friendly in terms of decreasing the treatment duration.…”
Section: Introductionmentioning
confidence: 99%